Prophylaxis in Children with Hemophilia: Evidence-Based Achievements, Old and New Challenges - Coppola, Antonio; Tagliaferri, Annarita; Di Capua, Mirko; Franchini, Massimo (Seminars in Thrombosis and Hemostasis, 2012)
Recurrent joint bleeding leading to progressive musculoskeletal damage (hemophilic arthropathy), in spite of on-demand replacement with deficient factor concentrates, is the clinical hallmark of severe hemophilia A and B (i.e., the congenital deficiencies of coagulation factors VIII and IX with circulating levels <1 IU/dL). Fifty years of clinical experience, which began in Northern Europe and then initiated in other European countries and in North America, up to the recent randomized clinical trials, have provided definitive evidence that preventing bleeding from an early age through long-term regular prophylactic concentrate infusions limits the adverse clinical consequences of arthropathy and its complications in the quality of life of hemophilic children. Primary prophylaxis started after the first joint bleed and/or before the age of 2 is now the evidence-based, first-choice treatment in severe hemophilia. Interestingly, recent data also suggest a role for early prophylaxis in preventing inhibitor development, the most serious complication of hemophilia therapy. Secondary prophylaxis is aimed to avoid (or delay) the progression of arthropathy. The earlier the treatment is started, the better the outcomes in joint status and quality of life. Although prophylaxis has radically transformed the natural history of severe hemophilia, relevant barriers to its implementation and diffusion remain. Beyond the obvious economic constraints and problems with venous access and long-term adherence, uncertainties regarding the optimal prophylaxis regimen require further evaluation in prospective studies to optimize approaches based on definite outcome measures and cost-effectiveness/cost-utility analyses. Scientific evidence, current clinical strategies, and open issues of prophylaxis in children with hemophilia will be addressed in this review.
Keywords: bleeding; children; hemophilia; hemophilic arthropathy; prophylaxis; quality of life